UNDANG - UNDANG TINDAK PIDANA KEKERASAN SEKSUAL DALAM PEMENUHAN HAK KORBAN - Muhammad Gerald Arsy; Wiwin Yulianingsih (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Sexual violence is a serious crime that violates human rights and adversely affects the well-being of victims. Protecting the rights of victims of sexual violence is crucial to ensuring justice and recovery for victims. Therefore, the purpose of this study is to investigate the realization of the rights of victims of sexual violence according to the current legislation. This study uses legal analysis techniques Yuridis-Empiris in relation to legislation applicable to sexual violence. Various aspects related to the exercise of victims' rights, such as protection, rehabilitation and compensation, are analyzed in detail. In addition, the study also addresses related issues such as public awareness, education and access to support services. The results of the study show that the law on sexual violence recognizes the importance of protecting the rights of victims. Victim protection is governed by a number of mechanisms, including the provision of physical protection and access to effective legal systems. Victim rehabilitation is also considered an important part of recovery, along with psychological support, medical care and education. Protection of the rights of victims of sexual violence is an important part of legislation on sexual violence. This law provides an important framework for the protection, rehabilitation and compensation of victims. However, issues such as public awareness and access to services remain to be addressed. Better protection of victims' rights in the future will require cooperation between governments, community groups and individuals.